2013
DOI: 10.4161/sgtp.22087
|View full text |Cite
|
Sign up to set email alerts
|

Zizimin and Dock guanine nucleotide exchange factors in cell function and disease

Abstract: Zizimin proteins belong to the Dock (Dedicator of Cytokinesis) superfamily of Guanine nucleotide Exchange Factor (GEF) proteins. This family of proteins plays a role in the regulation of Rho family small GTPases. Together the Rho family of small GTPases and the Dock/Zizimin proteins play a vital role in a number of cell processes including cell migration, apoptosis, cell division and cell adhesion. Our recent studies of Zizimin proteins, using a simple biomedical model, the eukaryotic social amoeba Dictyosteli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…2325 DOCK RhoGEFs lack primary sequence homology with the DH domain and instead are characterized by a conserved Dock-homology region-2 (DHR-2; also called DOCKER, CZH2) that serves as the RhoGEF catalytic domain. DHR-2 domains exhibit no primary sequence homology to DH domains.…”
Section: The Discovery Of Rhogefs: Diverse In Numbers and Structurementioning
confidence: 99%
“…2325 DOCK RhoGEFs lack primary sequence homology with the DH domain and instead are characterized by a conserved Dock-homology region-2 (DHR-2; also called DOCKER, CZH2) that serves as the RhoGEF catalytic domain. DHR-2 domains exhibit no primary sequence homology to DH domains.…”
Section: The Discovery Of Rhogefs: Diverse In Numbers and Structurementioning
confidence: 99%
“…There are two distinct GEF families for Rho proteins: those of the diffuse B-cell lymphoma (Dbl) and dedicator of cytokinesis (Dock) families [10, 13, 14]. In the interest of space and to provide a focused review, emphasis will be on the Dbl GEFs.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies in mammalian cultured cells and Dictyostelium revealed the roles of Ziz in cell migration, development, cytokinesis and growth (Pakes et al, 2013), functions of Ziz in specific tissues and organs in multicellular organ- isms are still not fully understood. In the present study, we revealed that Ziz-knockdown in eye imaginal disc induced the decrease of pigments in adult compound eyes that are associated with increase of SPC-and TPC-like cells with aberrant morphology and orientation in pupal retinae.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Zir appears to be necessary to activate Rac2 and Cdc42 during the cellular immune response in Drosophila (Sampson et al, 2012). Although studies in mammalian cultured cells and Dictyostelium revealed a role of Ziz in cell migration, development, cytokinesis and growth (Pakes et al, 2013), in vivo function of Ziz is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%